1999
DOI: 10.1046/j.1523-5378.1999.99286.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hpn and NixA of Helicobacter pylori in Susceptibility and Resistance to Bismuth and Other Metal Ions

Abstract: We concluded that bacteria lacking Hpn, cultured in vitro, are more susceptible than is the wild type to bismuth and Ni2+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
59
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 23 publications
6
59
0
Order By: Relevance
“…Hpn is also present in the ferret and cat gastric Helicobacter pathogens, but it is absent from the mouse (liver) pathogen H. hepaticus. H. pylori mutants lacking hpn were more sensitive to nickel and bismuth than the parent strain, but a nixA strain was not more sensitive; this indicates that Hpn may sequester metals that accumulate internally via a passive equilibrium mechanism (from a high external metals environment) (Mobley et al 1999). As nixA itself is regulated by nickel levels (through NikR) , it would seem to be of benefit to H. pylori to have Hpn proteins available to detoxify rapid fluxes in metal levels.…”
Section: Hpn and Hpn-like Proteinsmentioning
confidence: 98%
See 1 more Smart Citation
“…Hpn is also present in the ferret and cat gastric Helicobacter pathogens, but it is absent from the mouse (liver) pathogen H. hepaticus. H. pylori mutants lacking hpn were more sensitive to nickel and bismuth than the parent strain, but a nixA strain was not more sensitive; this indicates that Hpn may sequester metals that accumulate internally via a passive equilibrium mechanism (from a high external metals environment) (Mobley et al 1999). As nixA itself is regulated by nickel levels (through NikR) , it would seem to be of benefit to H. pylori to have Hpn proteins available to detoxify rapid fluxes in metal levels.…”
Section: Hpn and Hpn-like Proteinsmentioning
confidence: 98%
“…To further explore the roles of these (hpn and hpn-like) genes, individual gene-disruption mutant strains were created, and a double mutant lacking genes for both these histidine rich proteins was also studied (Seshadri, Benoit, Maier, unpublished data, ASM Abstract 2005). Previous results showed that an hpn mutant is more sensitive to nickel than is wild-type (Mobley et al 1999). Recent preliminary studies (S. Seshadri and R. Maier, abstract D21, 105th general meeting ASM, 2005) indicate the Hpn-like protein also may play a role in nickel detoxification.…”
Section: Hpn and Hpn-like Proteinsmentioning
confidence: 99%
“…De novo synthesis of NikR was not required for the mutant phenotypes, because inhibition of translation by chloramphenicol or erythromycin had no effect (data not shown). Single or double mutant strains with deletions of genes involved in Ni 2ϩ transport (nixA [28] and exbBD tonB [36]), Ni 2ϩ storage (hpn and hpn-like [6,19,29,37]), and Ni 2ϩ efflux (cznABC [39]) also showed no changes in NikR-dependent regulation (data not shown). This contrasts with results from E. coli, where the Ni 2ϩ efflux protein RcnA impedes NikR activation under nickel-limiting conditions (23).…”
mentioning
confidence: 98%
“…Besides nickel, CorA can also transport cobalt and maybe ferrous iron (39). It has been shown that H. pylori is especially sensitive to cobalt (38), a metal which is not transported via NixA (T. Eitinger, personal communication).…”
mentioning
confidence: 99%
“…The uptake, toxicity, resistance, and regulatory capacities of transition metals, especially the roles of iron (4,5,52) and nickel (38,51), have been the subjects of several investigations of H. pylori. Since the role of nickel is ambivalent (it is toxic at higher concentrations but it is essential for urease activity), a delicate equilibrium of nickel uptake, storage, and incorporation into target enzymes is therefore necessary.…”
mentioning
confidence: 99%